Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras - Damron, Brittany N.; Pinto-Da-Rocha, Ricardo; Longhorn, Stuart J. (Zootaxa, 2018)
A new species, Eucynorta rooneyi sp. nov. (Opiliones, Cosmetidae), is described from Parque Nacional Cusuco, Cortés, Honduras, a tropical montane cloud forest habitat. This is the thirty-fifth species of Eucynorta Roewer, 1912, and is characterized by the combination of three sexually dimorphic characters in males: enlarged chelicerae, some armature on femur III and IV, and swollen basitarsi on leg I. This new species is distinct from other Eucynorta species due to its unique pattern of yellow markings on area I of the dorsal scutum, and unarmed free tergites with line markings.